2021
DOI: 10.48550/arxiv.2111.06427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncovering astrometric black hole binaries with massive main-sequence companions with Gaia

S. Janssens,
T. Shenar,
H. Sana
et al.

Abstract: Context. In the era of gravitational wave astrophysics and precise astrometry of billions of stellar sources, the hunt for compact objects is more alive than ever. Rarely seen massive binaries with a compact object are a crucial phase in the evolution towards compact object mergers. With the upcoming Gaia data release (DR3), the first Gaia astrometric orbital solutions for binary sources will become available, potentially revealing many such binaries. Aims. We investigate how many black holes (BH) with massive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The vast majority of the remaining black holes are not accreting enough material to show up in X-ray observations and are therefore called quiescent black holes. There are several ways to potentially detect these: microlensing is a promising technique (Paczynski, 1986;Wyrzykowski & Mandel, 2020), as are astrometric detections using Gaia data (Breivik, Chatterjee & Larson, 2017;Janssens et al, 2021). In addition, it has been suggested that periodic variability of the orbital periods of several close binaries is due to a quiescent black hole as a tertiary component (Qian, Liao & Fernández Lajús, 2008;Liao & Qian, 2010;Er-Gang et al, 2019;Wang & Zhu, 2021).…”
Section: Black Holes As Tracers Of Massive-star Evolutionmentioning
confidence: 99%
“…The vast majority of the remaining black holes are not accreting enough material to show up in X-ray observations and are therefore called quiescent black holes. There are several ways to potentially detect these: microlensing is a promising technique (Paczynski, 1986;Wyrzykowski & Mandel, 2020), as are astrometric detections using Gaia data (Breivik, Chatterjee & Larson, 2017;Janssens et al, 2021). In addition, it has been suggested that periodic variability of the orbital periods of several close binaries is due to a quiescent black hole as a tertiary component (Qian, Liao & Fernández Lajús, 2008;Liao & Qian, 2010;Er-Gang et al, 2019;Wang & Zhu, 2021).…”
Section: Black Holes As Tracers Of Massive-star Evolutionmentioning
confidence: 99%